Suara Anak untuk Dunia dengan Mengekspresikan Melalui Gambar dan Kata di Panti Asuhan Baitussalam Kabupaten Blitar - Khoirul Wafa; M. Choirul Huda; Jauharul Husna; Septi Nanda M; Anis Maisaroh; Nanda Saniyaroh; Dwi Astrid Mei S; Sevika Nindi A; Cici Widiana W; Rahmawati Tunggal M; Shofia Qurotun N; Earlynd Ragiel N.A; Nadia Walidatul K; Intan Nurlaily N; Elfanni Rieka S; Anisah Nurrohmah; Evrilya Anggi N; Syifaul Zulfa N; Wildan Alwi P; Dewi Munzalam M; Bagus Priowidodo; Ach Yusuf Hariawan; Novela Veni I. (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This article discusses the expression development activities and character education of children at the Baitussalam Orphanage in Blitar Regency through a social service program with the theme "Children's Voices for the World Through Pictures and Words." This program is designed by dividing into 2 groups, namely for children aged 10-14 years with a focus on public speaking training aimed at increasing self-confidence, communication skills, and courage to speak in public. Meanwhile, for children aged 5-9 years, activities include coloring and storytelling which aim to hone creativity and language skills in a fun and interactive way. In addition to these activities, there is also material related to character education, which is an integral part of this program to form positive attitudes and moral values from an early age. The approach used is tailored to the developmental stage of the child's age, so as to maximize their potential for expression through pictures and words, as well as foster self-confidence and social skills that are important for their future. This program demonstrates that the development of public speaking and creative expression through art and storytelling can be an effective medium in children's character education in an orphanage environment.